2009
DOI: 10.1534/genetics.108.094607
|View full text |Cite
|
Sign up to set email alerts
|

Selective Genotyping and Phenotyping Strategies in a Complex Trait Context

Abstract: Selective genotyping and phenotyping strategies are used to lower the cost of quantitative trait locus studies. Their efficiency has been studied primarily in simplified contexts-when a single locus contributes to the phenotype, and when the residual error (phenotype conditional on the genotype) is normally distributed. It is unclear how these strategies will perform in the context of complex traits where multiple loci, possibly linked or epistatic, may contribute to the trait. We also do not know what genotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 21 publications
(28 reference statements)
0
20
0
Order By: Relevance
“…Thus the power and accuracy of QTL analysis improves when the selection is more finely targeted using prior knowledge. Sen et al [34] confirmed this but the efficiency of SP decreased as the number of unlinked loci considered increased. According to the authors, when only a small sample can be phenotyped, the efficiency of the SP is still higher compared to random sampling, even when more than ten loci are used for the selection.…”
Section: Effect Of Sampling Strategy On the Detection And Mapping Of mentioning
confidence: 87%
“…Thus the power and accuracy of QTL analysis improves when the selection is more finely targeted using prior knowledge. Sen et al [34] confirmed this but the efficiency of SP decreased as the number of unlinked loci considered increased. According to the authors, when only a small sample can be phenotyped, the efficiency of the SP is still higher compared to random sampling, even when more than ten loci are used for the selection.…”
Section: Effect Of Sampling Strategy On the Detection And Mapping Of mentioning
confidence: 87%
“…Studies of response to selection (Gallais et al 2009;) and selective genotyping, i.e., genotyping only individuals from the high and low tails of the phenotypic distribution (Lebowitz et al 1987;Navabi et al 2009;Sen et al 2009), were reported to be effective even for the detection of quantitative trait loci (QTL). However, the identification of QTL for the selected trait (DG) and estimation of their effects was beyond the scope of this study.…”
Section: Genetic Structure Of the Selected Linesmentioning
confidence: 99%
“…However, with large numbers of selection candidates in the female population, a preselection of genotyped animals is needed to optimize genotyping costs (Blonk et al, 2010). Selective genotyping of the most informative individuals might increase genotyping efficiency (Spangler et al, 2008;Sen et al, 2009). However, there has been very limited research as to which animals are most informative in terms of single-nucleotide polymorphism (SNP) effects and genomic predictions when females are used in the reference population.…”
Section: Introductionmentioning
confidence: 99%